Rationale, Design, and Baseline Characteristics of the EPICOR Asia Study (Long‐tErm follow‐uP of antithrombotic management patterns In Acute CORonary Syndrome patients in Asia). Issue 9 (24th July 2015) - Huo, Yong; Lee, Stephen W.‐L.; Sawhney, Jitendra P. S.; Kim, Hyo‐Soo; Krittayaphong, Rungroj; Nhan, Vo T.; Alonso‐Garcia, Angeles; Han, Ya Ling; Ge, Junbo; Chin, Chee Tang; Ong, Tiong K.; Jan, Stephen; et al.
ABSTRACT Background In‐hospital and postdischarge mortality for acute coronary syndromes (ACS) vary across Asia and remain generally poorer than globally. The relationship between real‐life antithrombotic management patterns (AMPs) and ACS‐related outcomes in Asia is unclear. Methods EPICOR Asia (Long‐tErm follow‐uP of antithrombotic management patterns In acute CORonary syndrome patients in Asia) (NCT01361386) is a prospective, multinational, observational study of patients discharged after hospitalization for an ACS, with 2‐year follow‐up. The aim is to describe short‐ and long‐term (up to 2 years post–index event) AMPs in patients hospitalized for ACS and to record clinical outcomes, healthcare resource use, and self‐reported health status. Pre‐ and in‐hospital management, AMPs, and associated outcomes, with particular focus on ischemic and bleeding events, will be recorded during the 2‐year follow up. Results Between June 2011 and May 2012, 13 005 patients were enrolled. From these, 12 922 patients surviving an ACS (6616 with STEMI, 2570 with NSTEMI, and 3736 with UA) were eligible for inclusion from 219 hospitals across 8 countries and regions in Asia: China (n = 8214), Hong Kong (n = 177), India (n = 2468), Malaysia (n = 100), Singapore (n = 93), South Korea (n = 705), Thailand (n = 957), and Vietnam (n = 208). Conclusions EPICOR Asia will provide information regarding clinical management and AMPs for ACS patients in Asia. Impact of AMPs on clinical outcomes, healthcare resource use, and self‐reported health status both during hospitalization and up to 2 years after discharge will also be described.